Development of Emotional Intelligence Instruments for Elementary School Students - Dewi, Rahma; habibi, mhmd; Wandri, Rades; Vebrianto, Rian (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2024)
Research instruments are the most important element in research. With a valid research instrument, the results of the research will be valid as well. But if the instruments or research tools used in the study are not effective, then the results obtained are certainly not as expected. Survey equipment is used to measure the subject of survey variables. Apart from that, the use of instruments in research is to collect data. This study was used to test the emotional intelligence that has been developed by researchers. The developed emotional intelligence instrument consists of five indicators, namely: 1) the ability to recognize oneself, 2) the ability to manage emotions, 3) the ability to motivate oneself, 4) the ability to recognize the emotions of others, and 5) the skill of cultivating relationships with others. This research is a research and development (Research and Development) involving 60 respondents, namely students of class V MIN 6 Central Tapanuli who were selected by stratified sampling and random. The data were analyzed using SPSS version 26.00 for Windows to confirm internal consistency with Cronbach Alpha. From the questionnaire results, the questionnaire items are valid and reliable, and the average reliability value of Cronbach's alpha is high (0.720 > 0.6), and this emotional intelligence index is used to measure the emotional intelligence of elementary school students.